Comparison of the Morphometric Traits and Body Weight of Pure Kampung Chicken with Kampung-Bangkok Crosses Chicken - Raodatul Jannah; Junaedi; Khaeruddin; Bahri Syamsuryadi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
Efforts that can be made to improve the performance of native chickens are by crossing them with Bangkok chickens. The results of crosses between Kampung chickens and Bangkok chickens are expected to pass down good growth genes. This study used 66 chickens consisting of 33 pure Kampung chickens and 33 chickens from the Kampung x Bangkok cross-reared from DOC until the age of eight weeks. Every week body weights and measurements of body parts are carried out. This study was analyzed using the T-test to compare the performance of chickens from the Kampung x Bangkok cross with native chickens. Body weights between native chickens and Kampung x Bangkok crosses were significantly different at the age of DOC (0 weeks) and the age of 3 to 8 weeks. Body length and height of free-range chickens with Kampung x Bangkok crosses were different at the age of DOC up to 2 weeks. Chest width was different between native chickens and Kampung x Bangkok crosses at DOC to 1 week of age. The Shank length and shank circumference of native chickens with Kampung x Bangkok crosses were different at all ages. The tibia length of free-range chickens with the Kampung x Bangkok cross was different at DOC up to 6 weeks of age. The tibia circumference of free-range chickens with Kampung x Bangkok crosses differed from DOC to 4 weeks of age.